Sob o régio braço: a Real Extração e o abastecimento no Distrito Diamantino (1772-1805) - Régis Clemente Quintão (2017)
In the second half of the eighteenth century, under the Josefino-Pombaline government, the Portuguese Overseas Empire underwent intense socioeconomic transformations. In this context, the principles of rationalization of administrative and fiscal practices became evident and gave rise to institutions that sought to intensify control over state revenues and expenditures. The Royal Diamond Extraction, managed by authorities residing in Lisbon and in the Captaincy of Minas Gerais, more precisely in the Diamantino District, was created by retaking dominance over mineral wealth, namely diamonds. In order to manage the diamond production and the associated costs, it was fundamental to organize a thriving supply entailing anything else necessary for the mining works and for the survival of the thousands of slaves and employees of the institution. The present dissertation deals with the control of this supply by the Royal Diamond Extraction itself. Based on unpublished manuscript sources belonging to the Historical Archives of the Portuguese Court of Auditors, we found that this control was sufficiently effective: despite the difficulties in containing expenses and executing orders issued by the Kingdom, no problems that could possibly endanger the continuity of diamond extraction surfaced from this operation. While the Royal Diamond Extraction supply demanded large quantities of imported goods, it did not prevent the stimulation of local trade and production. Thus, the control of supply reflected the very dynamics of this era, which relied on the notions of good administration not only to augment the riches of the Crown, but also to sustain the public happiness of its subjects.